Genome mining for glycoside hydrolases from the psychrophilic yeast Glaciozyma antarctica PI12 - Nooraisyah, M.N.; Siti Nur Hasanah, M.Y.; Mahadi, N.M.; Abu Bakar, F.D.; Murad, A.M.A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Glycoside hydrolases are enzymes that hydrolyse glycosidic bonds in carbohydrate chains to produce simple molecules. In fungi, glycoside hydrolases are important enzymes that hydrolyse complex carbohydrates into simple sugars that can subsequently be consumed for energy metabolism. Glaciozyma antarctica is a psychrophilic yeast isolated from sea ice in Antarctica. The G. antarctica genome has been completely sequenced, and a total of 7,857 genes have been predicted. The objective of the present study was to determine different classes of glycoside hydrolases from the G. antarctica genome and predict the localisation of these enzymes. Using genome mining, a total of 97 G. antarctica genes were predicted to encode glycoside hydrolases. The majority of the enzymes, including endoglucanases, xylanases, and chitinases, were identified from GH family 5 (12 genes), followed by GH family 45 (11 genes), GH family 10 (11 genes) and GH family 18 (9 genes). The secreted glycoside hydrolase enzymes were primarily endoglucanases from GH family 45, and these enzymes degrade celluloses in the cell walls of plants and algae. Extracellular glycoside hydrolases have been implicated as important in nutrient scavenging and organic decomposition in Antarctic sea ice.